MANAGEMENT OF POST TRAUMATIC SYMPTOMS WITH PRE-TRAUMATIC VULNERABILITY: Post Traumatic Symptoms - Malik, Wajid; Ali, Sohail; Rana, Mowadat Hussain (Pakistan Armed Forces Medical Journal, 2006)
IntroductionOn Oct 08, 2005, an earthquake measuring 7.6 on the Richter scale struck the northern parts of Pakistan followed by number of aftershocks. Mental health clinics were established in the affected areas after the disaster as there was rudimentary or absent pre disaster mental health facilities.Individuals who experience or simply witness traumatic events can develop posttraumatic reactions [1]. It has been shown that after a catastrophic natural disaster, post-traumatic reactions in children may reach epidemic proportions, remain high for a prolonged period, and jeopardize the well being of the child population of the affected region [2]. There is ample evidence that personality structure and experience such as neuroticism or childhood adversity in the period before the traumatic event also influence the risk of developing posttraumatic disorders [3].Once basic needs are regained such as food, clothing, and shelter, help is needed for the emotional and psychological well being of survivors.This case report describes importance of early detection and problems associated with assessment as well as diagnosis of Posttraumatic symptoms in children. Description includes relationship of trauma history with psychopathology and various strategies for management of posttraumatic symptoms in children and adolescents after natural disaster. To our knowledge this is the most comprehensive case study of an adolescent with posttraumatic stress symptoms after a natural disaster such as earthquake.The patient discussed has read this manuscript and has provided written informed consent for the publication of the material presented.